The Influence of e-Commerce Live Streaming on Purchase Interest in Muslim Fashion Products in Indonesia With Perceived Risk as an Intervening Variable - Devi Mustikawati; Muhammad Sholahuddin (Jurnal Ilmiah Mizani: Wacana Hukum, Ekonomi Dan Keagamaan, 2024)
The purpose of this study is to analyze the effect of e-commerce live streaming on purchase interest in Muslim fashion products in Indonesia with perceived risk as an intervening variable. This research method is a quantitative method. This study used primary data. The population of this study is the audience of e-commerce live streaming throughout Indonesia. The sample size of this study was 150 respondents. The sampling technique used is purposive sampling. The method of collecting this research data is a questionnaire.  The analysis technique used is Partial Least Square (PLS) with a calculation process using the SmartPLS 3.0 software program. The result of this study is that E-commerce Live Streaming has a significant positive effect on Purchase Interest. E-commerce Live Streaming has a significant positive effect on Perceived Risk. Perceived Risk has a significant positive effect on Purchase Interes